The Role of E-WOM Credibility and Online Engagement in Shaping Online Purchase Intention: An Empirical Study - Tri Andari Ratna Widyastuti; Audra Fahrezy Putra (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to analyze the influence of electronic word of mouth (eWOM) credibility and online engagement intentions on online purchase intentions among e-commerce consumers in Indonesia. This study uses a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis techniques. Respondents totaled 198 people who were selected purposively, with the criteria of active social media users and having made e-commerce transactions in the last three months. The results show that eWOM credibility and online engagement intentions have a positive and significant effect on online purchase intentions. This research contributes to the development of digital marketing strategies and enriches the literature on consumer behavior in the digital context.